Modified atmosphere packaging for fresh-cut fruits and vegetables - Brody, Aaron L.; Zhuang, Hong; Han, Jung H. (Wiley-Blackwell, 2011)
"Modified atmosphere packaging for fresh-cut fruits and vegetables provides comprehensive coverage of all aspects of modern MAP technologies for fresh-cut fruits and vegetables. Coverage begins with the general MAP concept and application by introducing the concept of MAP, how MAP works for fresh-cut produce and the benefits and shortfalls of MAP in its application. The book then discusses the basic aspects of MAP - packaging materials and machinery. In these sections, the book addresses not only the general information about MAP materials, but also supplies examples to introduce the new packaging films and their successful application in produce and fresh-cut fruits and vegetables. Unique chapters and sections in the book include relevant patents for MAP, commercial practices and MAP packaging machinery. Generally, packaging machinery is only included in books specifically covering packaging engineering. Coverage of this important aspect is included in the book since fresh-cut manufacturers spend much more time in the day-to-day operations on packaging machinery and systems as compared to packaging film materials. In the final section, Modified atmosphere packaging for fresh-cut fruits and vegetables highlights the latest developments in the packaging industry and how they could impact the fresh-cut industry"--Resumé vydavatele
Keywords: ovoce; zelenina; balení potravin; obalová technika; fruit; vegetables; food packaging; packaging; kolektivní monografie; elektronické knihy; collective monographs; electronic books